Design and fabrication of a corn extractor / Dennis Ngang Jaya, Sali Lawei and Marin Jiram - Ngang Jaya, Dennis; Lawei, Sali; Jiram, Marin (1985)
During the stone ages, man survives by hunting. He roams in the wilderness in some hopes to find some wild edible foods to eat. His movements depend solely on the availability of foods around him. He never settle down at one place. In another word, he is nomadic.